A modified co-production framework for improved cross-border collaboration in sustainable forest management and conservation of forest bird populations - Maggie MacPherson; Andrew Crosby; Shawn Graff; Linnea Rowse; Darren Miller; Ana Raymundo; Jacquelyn Saturno; Darren Sleep; Kevin A. Solarik; Lisa Venier; Yan Boulanger; Duane Fogard; et al. (The Forestry Chronicle, 2024)
The border between Canada and the United States poses jurisdictional challenges when it comes to consistently implementing science-based conservation of forests and their biological communities. Through a partnership with the Sustainable Forestry Initiative, Boreal Avian Modelling Project, and American Bird Conservancy, we developed a co-production framework to conduct research that will inform forest management practices for bird conservation in the cross-border region of Bird Conservation Region 12. Our framework first responds to the needs of resource managers and other perceived stakeholders, while investing in relationship-building for long term trust as a foundation for future partnerships with Indigenous rights holders and landowners. Our central question was: How can sustainably managed forests create and/or maintain high quality breeding habitat to support forest bird populations that are resilient to climate change? Engaging with experts in Canada and the United States, we found that the main driver for addressing our central question was our limitation in connecting bird population responses to specific forest management practices. We describe how experts are contributing avian count and forest inventory data that researchers will use to produce a requested decision-support tool. We continue to engage with land managers to link forest resource inventory data to specific forest management practices and refine the components of products by including more diverse perspectives.